ANALYSIS OF FACTORS AFFECTING THE FINANCIAL PERFORMANCE OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Firdaus, Syntia; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to provide empirical evidence of the impact of Good Corporate Governance (GCG), Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), and firm size on financial performance. The population used in this study is banking companies listed on the Indonesia Stock Exchange (IDX) during 2018 to 2020. The sample selection method used is purposive sampling. The companies used as research objects are as many as 31 companies. The research method used in this research is multiple linear regression analysis. The results obtained from this study are Good Corporate Governance (GCG) has insignificant and positive effect on financial performance, Capital Adequacy Ratio (CAR) has insignificant and negative effect on financial performance, Non-Performing Loan (NPL) has significant and negative effect on financial performance, and firm size has significant and negative effect on financial performance.